Assessment of students' knowledge on iodine supplementation by women planning pregnancy - Obuchowska, Aleksandra; Wójcik, Justyna; Standyło, Arkadiusz; Obuchowska, Karolina; Ozga, Alicja; Kimber-Trojnar, Żaneta; Leszczyńska-Gorzelak, Bożena (Journal of Education, Health and Sport, 2020)
Introduction: Iodine is essential for the synthesis of the thyroid hormones. Proper thyroid function in a pregnant woman depends on the accumulated reserves of iodine in the pre-pregnancy period. If they are sufficient, the production of thyroid hormones is adequate even in the case of increased demand. Adequate iodine status during pregnancy is crucial for maternal health and foetal growth. Severe iodine deficiency causes maternal and foetal hypothyroxinaemia, leading to irreversible brain damage, manifested by mental retardation and neurological disorders. The daily requirement for iodine for pregnant women has been determined by The World Health Organization (WHO) at 250 µg. Most likely, the demand for it cannot be covered only by dietary iodine intake, so iodine should be supplemented in the form of tablets at a dose of 150-200 µg daily. Purpose: The aim of the study is to assess students' knowledge on iodine supplementation by women planning pregnancy and pregnant women. Material and method: Students' knowledge regarding the importance of iodine supplementation was verified using anonymous Internet questionnaire. The obtained results were analysed and checked on the basis of scientific literature. Results: The percentage of students who think iodine supplementation should be recommended is 22.7%, and 9.7% believe it is not necessary. Only 8.8% of the respondents chose the correct recommended dose of iodine. Surprisingly, most of the respondents do not know the recommended iodine dose, as much as 71.7% of them. Conclusions: The proper supply of iodine has a decisive impact on the proper functioning of the body, and its deficiency has serious consequences, especially in the womb. The problem of iodine deficiency is serious. This is also confirmed by the results of our surveys. It is important to educate students on the recommendations for iodine supplementation in women of childbearing age.